Utilization of Google Glassroom in Islamic Religious Education in Higher Education during the Covid 19 Pandemic - Sittika, Achmad Junaedi; Bintang Kejora, Muhamad Taufik (Jurnal Pendidikan Indonesia, 2022)
The Covid-19 pandemic condition requires teachers to use technology in online learning. This study analyses the planning, implementation and evaluation of Islamic religious education assisted by Google class media. This research was conducted using a qualitative descriptive method involving 87 students. Data was collected through surveys, interviews, documentation, and observations. Data analysis was carried out using qualitative descriptive techniques and triangulation. The results showed that the use of Google Classroom in learning Islamic Religious Education gradually improved the quality of learning. It is supported by good planning, competent teaching skills, systematic learning implementation, and measurable evaluation. The learning process is democratic, humanist and technological. Students are given initiative, innovation, and creative freedom to foster motivation, awareness, independence, and togetherness in learning. On the other hand, they were encouraging learning objectives by implementing strict lecture contracts and sanctions for students who ignore agreed learning. Online learning using Google classroom can improve the quality of teaching lecturers, interaction or student activities in learning, discipline, timeliness of assignments, several responsible students, student attendance in meetings through Google Meet, student interaction in learning, and student learning outcomes.